Revitalisasi Sastra Lisan Bajo dalam Meningkatkan Identitas dan Daya Saing Pariwisata - Aisyah, Nur; Hesti; I Wayan Sudarsana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The purpose of this study is to determine the revitalization of Bajo oral literature so that it is easier to understand by the local community, especially young men and women in the Mola Bajo village in Waktobi. The research method uses a qualitative semiotic ethnographic approach and uses descriptive and interpretative data collection using semiotic theory in the form of icons, indexes, and symbols. The results of the study show that the Bajo community considers the sea as a source of life. This is what makes the sea an icon in the Bajo community. The signifier imbu is present as an index that shows a natural relationship that gives rise to cause and effect. Imbu is believed to be a sea creature that has great power and is able to sink ships if the sea is not respected. In addition, the Bajo oral tradition also believes in healing rituals through; Kaka, Kuta, Tuli. These three rituals are verbal symbols of the Bajo community which are believed to be healing rituals and birth processes, but both are still interconnected with each other. The conclusion is that the existence of semiotic analysis helps us to understand the identity of Bajo culture so that it can be integrated into Bajo cultural tourism objects in Waktobi. Keywords: Bajo Oral Literature, Cultural Tourism, Revitalization, Semiotics.